Vancomyciin Resiisttance among Metthiicii ll ll iin Resiisttantt Sttaphyllococcus aureus IIsollattes ff rom Generall Hospii ttalls - Abdul-Hameed, Rashad A.; Ayoub*, Nedhal S. (AL-Kindy College Medical Journal, 2014)
Bac kground:: Multidrug resistant methicillin-resistant Staphylococcus aureus (MRSA) is a major cause of nosocomial and community acquired infections. The glycopeptides vancomycin has been proposed as the drug of choice for treating such infections; this lead to the emergence of vancomycin intermediate sensitive S. aureus (VISA) and vancomycin resistant S.aureus (VRSA).Objjec tt iiv es :: To identify the vancomycin resistance both phenotypically and genotypically among MRSA isolates from different hospitals and to determine the sensitivity of these isolates to different antimicrobial agentsMetthods:: A total of 204 S. aureus isolates were obtained randomly from various clinical specimens including (wound swab, burn swab, ear swab, urine, sputum, blood and other body fluids) from different inpatient and outpatient who were attending different hospitals in Baghdad. The susceptibility pattern of the S. aureus isolates to different antibiotics was determined by disk diffusion method and vancomycin minimum inhibitory concentration (MIC) for MRSA isolates were determined using broth dilution method following clinical laboratory standard institution (CLSI) guidelines. Van A gene was amplified by PCR using standard primers. Res ull tts :: All VRSA isolates were MRSA. Twelve VRSA isolates were positive for van A gene, while the remaining ten isolates were negative. All VRSA had a vancomycin MIC of 16μg/ml or more. In the present study, VRSA showed resistance to a wide range of antimicrobial agents (Ampicillin, Cefalothin, Cefoxitin, Erythromycin, Gentamycin, Oxacillin, Penicillin, Rifampin, Tetracycline and Trimethoprim). Conc llus iions :: There were high incidences of resistance to the commonly used antibiotics among VRSA isolates compared to VISA and VSSA. Further molecular studies such as PCR technique to identify genes rather than van A (e.g van HAX analogue) might be suitable to predict VRSA lacking the van A gene